"Composable Capability" – Principles, strategies and methods for capability systems engineering. Issue 1 (June 2013) - Sillitto, H G
Abstract: Current systems engineering approaches for Capability Systems Engineering are difficult to understand and are not deployed consistently. Language is a barrier to understanding. A top‐down approach to "capability" still seems intractable. The traditional system focus of defence acquisition has been the "equipment". Force elements have been constructed bottom up from equipment. Inevitably such bottom‐up integration leads to unintended emergent properties in operational "force elements". This paper proposes that: improved operational readiness, performance and interoperability can be achieved by applying a systems engineering methodology in which the "system focus" is the force element, not the individual equipment; it is possible to identify a finite set of stable, well characterised building blocks (Force Elements) from which a wide variety of task force structures can be put together, providing almost infinite variety of capability solutions; that by thus re‐framing the problem we can contain the complexity explosion, giving more benefit with less difficulty; and that using such an approach top‐down will allow better statements of need, requirements and acceptance criteria to be passed to the acquisition community and supply chain.